Characterization of Halotolerant Bacillus Species Isolated from Salt Samples Collected from Leather Factories in Turkey - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2019)
Salt curing is the method most commonly utilized in the leather industry to prevent microbial growth on raw hides/skins. Despite this processing, a wide diversity of microorganisms belonging to Domains Bacteria and Archaea have nevertheless been observed on salted hides/skins. In order to understand whether halotolerant bacterial species in salt contaminate hides/skins during the curing process, 30 salt samples collected from 14 leather factories in Corlu and Tuzla (Turkey) were examined for halotolerant bacteria. Total counts of halotolerant bacterial numbers, pH values and moisture contents of the salt samples were respectively determined between 10(4)CFU/g and 10(6)CFU/g, 6.23 and 7.22, 0.90 and 5.02. All isolates were able to grow on both Nutrient Agar Medium without NaCl and Nutrient Agar Medium containing NaCl at concentrations ranging from 2 to 10%. The microorganisms isolated from the samples were identified using phenotypic characteristics and comparative partial 16S rRNA gene sequence analysis. The phylogenetic analysis, using more than 1300 base comparisons of 16S rRNA sequence data, revealed 83 halotolerant isolates that share highly similar identities (97.82-100%) with their closest phylogenetic relatives. These isolates were assigned to 12 different Bacillus species (B. amyloliquefaciens, B.atrophaeus, B.halotolerans, B. licheniformis, B.mojavensis, B.paralicheniformis, B.pumilus, B.safensis, B.siamensis, B.subtilis, B.tequilensis, B.velezensis). We detected catalase and protease activities, as well as production acid from fructose, in all Bacillus isolates. Fifty-five isolates demonstrated positive oxidase activities, and 50 isolates utilized citrate as a sole carbon source. While a fairly high percentage of the isolates produced acid from maltose, almost half of the isolates produced acid from myo-inositol. While 67% of the salt samples contained 1-2 different Bacillus species, 33% of the salt samples contained 3-4 different Bacillus species. Although B.amyloliquefaciens, B.atrophaeus, B.safensis, B.siamensis species were detected at a few salt samples, B.paralicheniformis and B.halotolerans species were detected at more than half of the salt samples. These results uphold the hypothesis that proteolytic halotolerant Bacillus species in the curing salts may contaminate hides/skins during curing process. Hence, we recommend sterilized salts be used in the preservation of the hides/skins to prevent economic losses in the leather industry.
Keywords: SP-NOV.; SUBTILIS; DIVERSITY; BACTERIA; SEQUENCE; PROPOSAL; STRAINS